'Bad' mums tell the 'untellable': Narrative practices and agency in online stories about postnatal depression on Mumsnet. (October 2018) - Jaworska, Sylvia
Highlights: This study explores narrative practices in online exchanges about PND. Results show the use of two canonical narratives: confession and exemplum. Confession acts as a way into disclose PND. Exemplum is a tool of alignment and validation. Technosocial factors and narrative practices online lead to transformations offline. Abstract: Health research highlights transformative and therapeutic effects of peer-to-peer online communication. Yet, we still know little about the practices and processes that generate such effects. This paper seeks to contribute to this understanding by examining polylogue online stories about postnatal depression (PND) on the popular parenting website Mumsnet. Drawing on the notion of narrative, small stories and positioning, this study shows how a narrative discourse-analytical approach can reveal narrative practices used to project and transform illness identities. At the micro level, the analysis shows that the small stories studied here draw on two big canonical narratives confession and exemplum . Whereas confessions are a 'way in' to disclose PND, the 'didactical' exempla serve as a knowledge resource and tools of alignment, and validation helping women to narratively repair 'spoiled' identity. At the macro-level, the analysis highlights tensions that exist between hegemonic discourses about motherhood and personal PND stories in which women appropriate and re-work these discourses to break silence and exercise agency. This study shows how together with technosocial factors these narrative practices can work to produce transformative effects of trouble telling and sharing online and contributes to a better understanding of digital practices underlying peer-to-peer interactions about stigmatised conditions.